O gênero acadêmico: resumos nas áreas de Antropologia, Linguística e Ciência Política - Gil, Beatriz [UNESP] (2014)
The purpose of this research is to compare 71 research article abstracts taken from six Qualis A1 journals of Anthropology, Political Science and Linguistics. Our intention is to observe possible rhetorical and linguistics differences of the genre abstract among the disciplines. As methodology, Gil’s model (2011) was used to analyze the rhetorical structures. The results show a rhetorical grouping that does not follow the disciplinary division. On one hand, three journals (2 Linguistics, 1 Anthropology) present similar characteristics: high recurrence of Methodology and Results moves, use of quantitative methods, with lab and microscopic analysis, and detailed description of results. On the other hand, the other three journals (2 Political Science, 1 Anthropology) present Step-by-step Move, interpretative and qualitative methods, and less detailed results. These results highlight the heterogeneity among disciplines and suggest that the subdisciplines and their boarders have great influence on abstracts